Sleep disorders in children with attention-deficit/hyperactivity disorder - Medina Permatawati; Agung Triono; Mei Neni Sitaresmi (Indonesian Pediatric Society, 2018)
Background Attention-deficit/hyperactivity disorder (ADHD) is a neurobehavioral abnormality that commonly occurs among children. Sleep disorders are comorbid with ADHD. Sleep disorders in Indonesian children with ADHD have not been widely studied.Objective To understand the proportion and factors that influence sleep disorders in children with ADHD. Methods This cross-sectional study involved 54 children aged 3-14 years who had been diagnosed with ADHD by a pediatric growth and development consultant using DSM-5 criteria. The subjects were consecutively selected from March to August 2017 at the Child Development Polyclinic, Dr. Sardjito Hospital, Yogyakarta. Sleep data were collected using the Sleep Disturbances Scale for Children (SDSC) and the Children’s Sleep Hygiene Scale (CSHS).Results Of the 54 children with ADHD (46 males and 8 females), 35 (64.8%) experienced sleep disorders. The majority (26 subjects, 48.1%) had the disorder of initiating and maintaining sleep. Children with the combined (inattention and hyperactive-impulsive) type of ADHD experienced significantly greater sleep disturbance compared to the inattention type or hyperactive-impulsive type (OR=3.750; 95% CI 1.133 to 12.41; P=0.027). Poor sleep hygiene was also significantly associated with more severe sleep disorders (r=-0.383, P=0.004).Conclusion The proportion of sleep disorder in children with ADHD is relatively high, with the majority having a disorder of initiating and maintaining sleep. Children with combined type ADHD experience a higher amount of sleep disorder than those with either the inattention or hyperactive-impulsive types of ADHD. Children with poor sleep hygiene have significantly more severe sleep disorders.